Psoriasis: correlation between severity index (PASI) and quality of life index (DLQI) in patients assessed before and after systemic treatment - Pereira da Silva, Maria Flavia [UNESP]; Parise Fortes, Maria Rita [UNESP]; Bartoli Miot, Luciane Donida [UNESP]; Marques, Silvio Alencar [UNESP] (Soc Brasileira Dermatologia, 2013)
BACKGROUND: Psoriasis is a chronic inflammatory disease of the skin that affects patients of all ages and both genders. The impact of the disease on quality of life is greater among patients with moderate to severe psoriasis. OBJECTIVE: to establish a correlation between the psoriasis area and severity index (PASI) and the Dermatology Life Quality Index (DLQI) based on a quality of life questionnaire adapted to the Brazilian context for patients with plaque psoriasis before and after systemic treatment. METHODS: This was a cross-sectional, descriptive study of psoriasis patients who did not undergo treatment or who manifested clinical activity of the disease. Patients were evaluated according to the PASI and the quality of life questionnaire adapted to the Brazilian context before and 60 days after systemic treatment. RESULTS: Thirty-five patients participated in the study. Twenty-six were men, with a mean age of 46 years. There was no correlation between the PASI and the quality of life questionnaire adapted to the Brazilian context, but there was a correlation between the PASI and some items of the quality of life questionnaire adapted to the Brazilian context, such as jobs involving public contact. CONCLUSION: The non-correlation between the PASI and the quality of life questionnaire adapted to the Brazilian context in this work may be associated with a history of chronic disease, which implies greater acceptance of the illness, or may be related to the low income and social status of the patients studied. The correlation observed among patients with careers involving public contact suggests that some professions are more impacted by the disease. It may be necessary to adapt the quality of life questionnaire to patients with a low income and cultural and social limitations. The small sample size (n=35 patients) and the short follow-up period of 60 days were some of the limitations of this work.
Keywords: Clinical evolution; Psoriasis; Quality of life; Quality of life indicators; Therapeutics